Different responses of soil bacterial community to plant–plant interactions under organic–inorganic fertilizers affect seedling establishment during subalpine forest succession - Li, Dandan; Kou, Yongping; Liang, Jin; Zhao, Wenqiang; Chen, Dongdong; Liu, Qing (Frontiers in Microbiology, 2024)
Introduction Rhizosphere bacterial community as a valuable indicator of soil quality and function, has been widespread studied. However, little knowledge is about the response of bacterial communities to plant–plant interaction and different fertilizers during secondary forest succession. Methods We conducted a field pot experiment applying organic and inorganic fertilizers to monocultures and mixed cultures of dominant plant species from mid- to late-successional stages (Salix oritrepha, Betula albosinensis, and Picea asperata), and investigated the responses of plant growth and rhizosphere bacterial communities. Results and discussion Results indicated that growth rate of plant height varied among plant species, but no significant differences were observed in soil bacterial diversity and composition among plant species or inter-specific interactions under control. Compared to control, inorganic fertilizer resulted in increases in plant growth and the relative abundance of Proteobacteria, Patescibacteria, Bacteroidetes and Gemmatimonadetes, while simultaneously leading to decrease in the relative abundance of Acidobacteria, Actinobacteria, Chloroflexi, Rokubacteria and Planctomycetes. When grown with other species, the bacterial communities in the mixture resembled those of S. oritrepha in singular monoculture under inorganic fertilizer treatment, but plant growth was not affected by interspecific interaction. Unlike inorganic fertilizer, organic fertilizer significantly affected bacterial communities and increased bacterial diversity, but did not alter the effects of plant–plant interactions on bacterial communities. It was also observed that organic fertilizer facilitated later successional species’ growth (P. asperata and B. albosinensis) by the mid-successional species (S. oritrepha), ultimately facilitating secondary forest succession. In addition, plants at different successional stages harbor specific bacterial communities to affect their growth, and the bacterial communities contributed more than soil properties to the variations in the plant growth of S. oritrepha and P. asperata though the bacterial communities were regulated by soil factors. This finding highlights the significance of the rhizosphere bacteria on plant growth and plant community succession. It also emphasize the importance of considering both plant–plant interactions and diverse fertilizer types in forest restoration efforts and provide valuable insights into optimizing agronomic practices for secondary forest succession.